Heidi. - Johanna, Spyri (First Avenue Classics (tm) Ser., 2015)
When Heidi's parents pass away, her aunt takes her in, but she soon sends Heidi to live with her grandfather in the Swiss Alps. At first, Heidi's grandfather seems gruff, but over time he becomes fond of her. Heidi grows to love the mountains and spends many hours with the goats and Peter, the goatherd, until she is sent to back to the city to be a companion to Clara, an invalid, and receive an education. Heidi learns that though the people in the city have more money, the people in the country lead richer lives. This classic Swiss children's book by Johanna Spyri was published in two parts in 1880 and 1881. This unabridged version comes from a 1915 edition, translated from the original German by Elisabeth P. Stork and illustrated by Maria L. Kirk. -- Provided by publisher.